Effect of skipping breakfast on cerebral blood flow and cardiovascular function under a mental load in healthy female students - Sawai, Asuka; Nie, Naoyo; Sawai, Shinya; Tsuzuki, Kayoko; Tochikubo, Osamu (Progress in Nutrition, 2020)
This study aimed to investigate the influence of skipping breakfast on the performance of a mental arithmetic load from the physiological viewpoint. In 16 healthy female university students who habitually eat breakfast, cerebral blood flow measured (CBF) by near-infrared spectroscopy, blood glucose, ketone bodies, autonomic nerve activity measured by electrocardiography, and energy expenditure measured by indirect calorimetry were monitored during a mental arithmetic load after eating and not eating breakfast, and cross-over evaluations were performed. The number of correct answers given to the arithmetic test; the levels of blood glucose, energy expenditure, and respiratory quotient; and the changes in deoxyhemoglobin in the CBF were significantly lower on the day breakfast was eaten than not eaten (p<0.05). In contrast, significant increases in ketone bodies, parasympathetic nervous system activity, and changes in the tissue oxygenation index in CBF were observed during the arithmetic test on the day breakfast was not eaten than eaten (p<0.05). Poorer performances, low levels of deoxyhemoglobin, and high levels of tissue oxygenation index in CBF were observed during mental loads in the students who skipped breakfast. This study suggested that physiologically, skipping breakfast may cause problems in academic performance.